From Waste to Strength: Applying Wastepaper, Fungi and Bacteria for Soil Stabilization - Darya A. Golovkina; Elena V. Zhurishkina; Alina T. Saitova; Mikhail V. Bezruchko; Irina M. Lapina; Anna A. Kulminskaya (Applied Sciences, 2024)
Biocementation is a promising soil stabilization technology that relies on microbiologically induced calcite precipitation (MICP). The addition of wastepaper was found to enhance the mechanical strength of biocemented soil. This study examined the effects of incorporating wastepaper into biocemented soil, focusing on the use of the ureolytic bacterium Bacillus licheniformis DSMZ 8782 and the yeast-like fungus Scytalidium candidum 3C for soil stabilization. The optimal wastepaper content was determined to be 2%, as it did not disrupt the uniform distribution of CaCO3 and contributed to improved soil strength. The combination of bacteria and fungi significantly increased the unconfined compression strength of samples containing 2% wastepaper (161.1 kPa) compared to untreated soil (61 kPa) and bacteria-only treatments (66.5 kPa), showing improvements of 2.6 and 2.4 times, respectively. Furthermore, we demonstrated that adding fungal biomass without wastepaper significantly improved the compressive strength, achieving a value of 236.6 kPa—nine times higher than untreated soil (26.4 kPa) and four times higher than soil treated with bacteria alone (60.6 kPa). This study identifies the optimal wastepaper content and highlights the potential of combining fungal and bacterial biomass for biocementation in soil stabilization.